Analysis of essential oil of Galium aparine. - Katarzyna Antoniak; Marlena Dudek-Makuch; Wiesława Bylka (Polish Pharmaceutical Society, 2019)
Summary Galium aparine L. (clivers, goosegrass) (Rubiaceae) is used in folk medicine as diuretic and medicinal plant alleviating different dermatoses as psoriasis, seborrheic dermatitis, eczema, and improves the immune system. So far, scientific studies have shown as a main constituents: iridoids (mainly asperuloside), flavonoids (luteolin, chrysoeriol, apigenin and quercetin derivatives), numerous of phenolic acids and phytosterols. Previous studies confirmed antimicrobial, antioxidant and cytotoxic activity of clivers. The aim of this work was to investigate the chemical profile of essential oil isolated from G. aparine collected in Poland. The essential oil was extracted from the herb of G. aparine by hydrodistillation in Deryng-type apparatus and the volatile constituents were identified by gas chromatography coupled with mass spectrometry (GC-MS). 0,1 ml of essential oil (3,33 ml/kg) was obtained from the of G. aparine herb, in which 74 volatile ingredients were identified (100%). According to GC/MS analysis 9-diazo-9H-fluorene (31,93%), palmitic acid and dihomo-γ-linolenic acid (8,89%) were as major constituents. 9-diazo-9H-fluorene is very rare in the plant world, previously identified only in Bidens pilosa. Terpene compounds represented 22,31% of essential oil, including 15 sesquiterpenes (18,23%), 6 monoterpenes (2,00%) and 1 diterpene (3,08%). The other active ingredients of the oil include: phytol, β-ionone, anethole, spatulenol, α-cadinol, phenylethyl alcohol, eugenol, methyleugenol, α-carvacrol, α-caryophyllene, α-terpineol, isoaromadendren epoxide, carvone, linalool, santalol, β-farnesene and eucalyptole. The ingredients of the essential oil are multi-directional activity - anti-inflammatory, antimicrobial, anti-cancer, antiproliferative, effect on angiogenesis, and also have occlusive properties. Quantify and a number of ingredients of the essential oil have proven that it may be one of the bioactive important fractions of the clivers herb and partly justify the traditional use of G. aparine.